1999
DOI: 10.1046/j.1365-2249.1999.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a whole blood assay to evaluatein vitroT cell responses to new leprosy skin test antigens in leprosy patients and healthy subjects

Abstract: Development of an immunological tool to detect infection with Mycobacterium leprae would greatly benefit leprosy control programmes, as demonstrated by the contribution of the tuberculin test to tuberculosis control. In a new approach to develop a 'tuberculin-like' reagent for use in leprosy, two new fractions of M. leprae depleted of cross-reactive and immunomodulatory lipids- MLSA-LAM (cytosol-derived) and MLCwA (cell wall-derived)-have been produced in a form suitable for use as skin test reagents. T cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
3
26
0
1
Order By: Relevance
“…A number of current initiatives therefore aim to develop new skin test reagents for leprosy. One approach is to fractionate the antigens of the leprosy bacillus to provide a skin test reagent (4); such fractions are highly antigenic but may not have the requisite specificity (30). Another approach is to identify synthetic peptide epitopes specific for M. leprae, which could be combined to give a reagent capable of inducing a positive skin test response in the majority of individuals from varying ethnic backgrounds and HLA types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of current initiatives therefore aim to develop new skin test reagents for leprosy. One approach is to fractionate the antigens of the leprosy bacillus to provide a skin test reagent (4); such fractions are highly antigenic but may not have the requisite specificity (30). Another approach is to identify synthetic peptide epitopes specific for M. leprae, which could be combined to give a reagent capable of inducing a positive skin test response in the majority of individuals from varying ethnic backgrounds and HLA types.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using M. leprae antigens fractionated on nitrocellulose indicated that many additional proteins might be recognized as antigens (4). It is also likely that within fractionated M. leprae preparations such as the M. leprae cell wall antigenic fraction and the M. leprae cytosolic antigen fraction, which induce strong T-cell responses in peripheral blood cells from tuberculoid leprosy patients (21,30), there are many as yet unidentified antigens. The objective of the current study was to utilize available genomic information from M. leprae to identify some of these additional, as yet unidentified antigens and, in particular, those which might be specific for M. leprae.…”
mentioning
confidence: 99%
“…IFN-␥ measurements in whole blood restimulation assays were performed as described previously (17,28,29). Briefly, 5 ml of blood was taken by venipuncture from each patient and immediately mixed with heparin at a concentration of 20 U/ml.…”
Section: Methodsmentioning
confidence: 99%
“…However, this test fails to detect the majority of PB/TT patients and HHCs, though these individuals present strong CMI responses to mycobacterial antigens (3, 13). Both in vitro gamma interferon release assays (IGRAs) and a simple delayed-type hypersensitivity skin test have been developed to detect individuals in the early stages of leprosy, using highly antigenic M. leprae fractions and the major individual immunogenic proteins (4,8,14,22,25). However, an obstacle in the application of IGRAs to the major M. leprae protein antigens is that most of these antigens share appreciable homology with orthologues in Mycobacterium spp.…”
mentioning
confidence: 99%
“…Since the presence of skin lesions in these patients is variable, their clinical symptoms are not sufficient to specifically diagnose leprosy (1). These problems are accentuated in the case of diagnosis of individuals with subclinical Mycobacterium leprae infection, including household contacts (HHCs) of leprosy patients, regarded as the primary source of ongoing leprosy prevalence (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%